A mente é a arma, a voz é a bala: problematizando o Programa Fica Vivo! como produtor de controle, normalizações e possíveis invenções de modos de vida - Marcus Otavio Mariani Nogueira (2011)
The discussion about public security is in the present-day a central subjective in Brazilian society and thinking it from the perspective of control and surveillance, of the territory and the youth in a public politic for crime prevention has relevance to the question to what extent the State can intervene and create devices for the discussion of public space, violence, crime and homicides. This study wanted to ask how the Estado de Minas Gerais, from Secretaria de Estado de Defesa Social (SEDS), your Superintendência de Prevenção à Criminalidade (SPEC) and the Programa Fica Vivo! analyze the spatial segregation, the territorial fights, conflict zones, the dominance and the interdiction of public spaces and producing areas of intolerance, from the young rivalry that culminates in a high number of homicides. Think what tools and how effective has the state to intervene on these issues. I wanted to analysis the use of a contradictory device that can enable control and standardization, and also able to produce forms of subjectivity. I instructed my analysis by Foucault, approaching his theoretical and using your conceptual tripod - knowledge, power and subjectivity - as major categories of analysis. I emphasized the field study and empirical observation. I wanted to think the slums and discuss the segregation of the territories in the city of Belo Horizonte. Analyze what is in the match in the productions of knowledge and power relations in the Programa Fica Vivo!. Think the power in their slips and how the workshops of the program can be understood as safety devices in your production of surveillance and control. From the contact with young people wanted to discuss how they produce and consume subjectivity, as established sociable relations. From the trajectory of a central actor in the politic, wanted to think the process of subjectivition. Reflect the production of assemblages of singularities able to escape from a knowledge-power regime.